2000
DOI: 10.4315/0362-028x-63.7.900
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Vibrio parahaemolyticus Isolates Obtained from Foodborne Illness Outbreaks during 1992 through 1995 in Taiwan

Abstract: Vibrio parahaemolyticus is an important foodborne pathogen in Taiwan and many other Asian countries. A total of 371 isolates of V. parahaemolyticus collected from patients involved in foodborne illness outbreaks in Taiwan from 1992 to 1995 were characterized. These isolates had typical biochemical characteristics and only 4% were urease positive. The most frequently isolated serovars were O5:K15 (18.5%), O4:K8 (16.2%), O3:K29 (12.5%), O1:K56 (8.3%), O2:K3 (6.5%), and O4:K12 (6.0%). Most of the isolates were su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
65
0
3

Year Published

2002
2002
2016
2016

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 102 publications
(71 citation statements)
references
References 15 publications
3
65
0
3
Order By: Relevance
“…Vibrio parahaemolyticus is a major, world-wide cause of gastroenteritis (Mead et al ., 1999;Wong et al ., 2000). It can be isolated as free-swimming planktonic cells from seawater or as cells attached to a variety of animate and inanimate surfaces (Kaneko and Colwell, 1975;Yamamoto and Yokota, 1989;Kumazawa et al ., 1991a,b).…”
Section: Introductionmentioning
confidence: 99%
“…Vibrio parahaemolyticus is a major, world-wide cause of gastroenteritis (Mead et al ., 1999;Wong et al ., 2000). It can be isolated as free-swimming planktonic cells from seawater or as cells attached to a variety of animate and inanimate surfaces (Kaneko and Colwell, 1975;Yamamoto and Yokota, 1989;Kumazawa et al ., 1991a,b).…”
Section: Introductionmentioning
confidence: 99%
“…9,10 Thermostable direct hemolysin (TDH) is a well-known exogenous toxin that is produced by clinical strains of V. parahaemolyticus. 5 Cell culture studies have shown that TDH is required to alter ion flux and to form pores in intestinal cell membranes. 11,12 Using a rabbit ileal loop model, Nishibuchi et al 13 demonstrated that fluid accumulation following infection with a tdh deletion strain was significantly reduced compared to the wildtype strain.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6] The main manifestation of V. parahaemolyticus infection is gastroenteritis with diarrhea, abdominal pain, vomiting, headache, fever and chills. 6 V. parahaemolyticus-induced diarrhea is inflammatory with edema, congestion of blood vessels, hemorrhage and increased level of neutrophils in the lamina propria of the intestine.…”
Section: Introductionmentioning
confidence: 99%
“…One of the most deadly food-borne pathogens, V. vulnificus, is the probable cause of the greatest number of seafood-related fatalities in the United States. Vibrio parahaemolyticus is less deadly, but causes a greater number of food-borne illnesses and can result in pandemic outbreaks of disease (Mead et al 1999, Strom and Paranjpye 2000, Wong et al 2000. Vibrio cholerae remains a major threat in many places around the globe as the causative agent of cholera, and its reservoir in the estuarine environment may play an important role in the survival and transport of pathogenic strains , Chakraborty et al 2000, Binsztein et al 2004 Previous studies have demonstrated strong relationships between Vibrio abundance and environmental conditions such as salinity, temperature, and attachment to planktonic organisms (Tamplin et al 1990, Heidelberg et al 2002, Lipp et al 2003, Louis et al 2003, Maugeri et al 2004.…”
Section: Introductionmentioning
confidence: 99%